Al Kalimãtu al Musta’ãratu al ‘Arabiyyatu fī “Jambi Malay Dictionary (Dialect of Jambi Seberang) Indonesia” (Dirãsatun Taḥlīliyyatun fī ‘Ilmi al Aṣwãti) - Rahmadini, Ayu; Prihartini, Yogia (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
This article aims to describe the process of phonological changes in Arabic loanwords in the